Peningkatan Kompetensi Istima’ wa Takallum Melalui Media Film - Rini, Rini; Yasmar, Renti (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This article discusses the problematics of Arabic learning. IAIN Curup Arabic Study Program students one of them is seen from the low competence of al-istima 'wa al-kalam students. The purpose of this study is to look at the competence of al-istima 'wa al-kalam students by using film media in learning al-istima' wa al-kalam, then the strategies used and the obstacles found in the learning process of al-istima 'wa al-kalam with film media. This research is descriptive qualitative. The results showed that the competence of al-istima 'wa al-kalam students was seen from the indicators of the achievement of al-istima' competence of wa al-kalam using film media divided into three categories of high, medium and low categories. From 34 students in the high category and currently dominating the ability of students who are aimed at 30% or as many as 12 students get high categories, 56% or as many as 19 students in the medium category, while 14% or 4 students are in the low category. The strategy of using film media in learning al-istima 'wa al-kalam uses several activities including grouping students in determining films to be discussed, screening films, collecting vocabulary that appears, reinterpreting films both oral and written. As for the obstacles faced in the use of film media in learning al-istima 'wa al-kalam namely the storyline and communication in the film are too fast so it needs to be repeated the screening of films in each episode as well as obstacles in technical matters such as constraints in facilities and infrastructure in the inadequate language laboratory.